2016
DOI: 10.1002/bdd.1996
|View full text |Cite
|
Sign up to set email alerts
|

A physiologically based pharmacokinetic model to predict the pharmacokinetics of highly protein‐bound drugs and the impact of errors in plasma protein binding

Abstract: Predicting the pharmacokinetics of highly protein-bound drugs is difficult. Also, since historical plasma protein binding data was often collected using unbuffered plasma, the resulting inaccurate binding data could contribute to incorrect predictions. This study uses a generic physiologically based pharmacokinetic (PBPK) model to predict human plasma concentration-time profiles for 22 highly protein-bound drugs. Tissue distribution was estimated from in vitro drug lipophilicity data, plasma protein binding, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…Since f up is also an important determinant of BP, when calculating tissue partitioning (K p values) from BP, errors in f up will largely cancel (Figure 2). This has been shown previously using a generic PBPK model to simulate the effect of plasma protein binding errors on V ss prediction (13). …”
Section: Tissue Partitioningmentioning
confidence: 56%
See 1 more Smart Citation
“…Since f up is also an important determinant of BP, when calculating tissue partitioning (K p values) from BP, errors in f up will largely cancel (Figure 2). This has been shown previously using a generic PBPK model to simulate the effect of plasma protein binding errors on V ss prediction (13). …”
Section: Tissue Partitioningmentioning
confidence: 56%
“…Poulin et al proposed an albumin-mediated transport mechanism that increases the extracellular concentration of drug at the plasma membrane (24), resulting in an increased intracellular concentration and increased clearance. We have recently reported that highly protein bound neutral and acidic drugs require a scaling factor of 12, whereas bases did not require a scaling factor (13). While this is consistent with an albumin-mediated uptake mechanism, in the absence of an active transport or an energy-dependent process, increased concentrations at the membrane cannot increase intracellular concentrations at equilibrium.…”
Section: Clearance Predictionsmentioning
confidence: 99%
“…to validate the ability to predict plasma concentration accurately (as the standard metric for PK). 0.84 3,5,62 3.69* 3.69*…”
Section: Rapid Repurposing Workflow Test Datasetmentioning
confidence: 99%
“…In light of, the LLOQ of this method was 13.7 nM, the free concentration in rat plasma expected may be very low based on the generally high plasma protein binding ratio of most of drugs which have high ClogP value. Compared to the agent's inhibitory concentration at 50% of efficacy (IC50) at 29.5 nM against PARP1, which was the free concentration of bromophenol-thiosemicarbazone hybrid, the LLOQ of 13.7 nM may keep sensitive for EC50 studies in vivo (Ye, Nagar et al 2016). In addition, bromophenol-thiosemicarbazone hybrid was expected to develop as an intravenous dosage form according to the results of IC50 in vitro in the future.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%